STUDY OF SUBSISTENCE FARMING COMMUNITY IN NORTH LINTAU BUO JORONG KAYU MERANTING - FATMA, AIDA; Rianto, M.Pd, Slamet; SE, M.Si, Nefilinda, (Pendidikan Geografi, 2014)
AbstractsThis study aims to determine the study of subsistence farming community in the District North Lintau Buo Jorong Kayu meranting viewed in terms of food, clothing, shelter, education and health. This type of research is a descriptive study. The population of this entire community residing in the District Lintau Buo Jorong Kayu meranting, amounting to a total of 275 heads of households, sampling techniques Proportionate random sampling study is the sample size of respondents to 137 people in the ellipse kayu meranting Lintau buo northern districts. Results showed subsistence farming community in oblong kayu meranting Lintau buo districts north of the results of field research with the provisions of the criteria can not afford, that is located on meeting the needs of food and clothing, subsistence farming community in the District North Lintau Buo Jorong Kayumeranting of the results of field research the criteria are less capable, which lies in the fulfillment of the needs and health boards and while the results are quite capable of data lies in meeting the needs of education.